Harmonic Bernoulli strings and random permutations - Manstavičius, Eugenius (Lietuvos matematikos rinkinys, 2004)
We examine fairly special b-harmonic Bernoulli strings appearing in n observations. It is shown that their count number can be used to define a random process converging to the Brownian motion as n tends to infinity. The proof is based upon the invariance principle for random permutations.